Efektivitas high-quality CPR terhadap survival pasien henti jantung di IGD dan perawatan kritis: A systematic review - Yeli Yulianti; Asep Robby (Holistik Jurnal Kesehatan, 2026)
Background: Cardiac arrest is a life-threatening emergency that requires immediate resuscitation. The quality of cardiopulmonary resuscitation (CPR) plays a crucial role in determining the success of return of spontaneous circulation (ROSC) and patient survival. Emergency and critical care nurses have a strategic role as first responders in initiating CPR; however, variations in CPR quality remain a challenge in clinical practice. Purpose:  To examine the effectiveness of high-quality CPR–based nursing interventions on outcomes of cardiac arrest patients in emergency and critical care settings. Method: Systematic review design following the PRISMA guidelines. Literature searches were conducted using PubMed, Scopus, CINAHL, ScienceDirect, and Google Scholar databases for articles published between 2019 and 2024. Eligible studies were systematically analyzed, and methodological quality was assessed using the Joanna Briggs Institute (JBI) Critical Appraisal Tool. Results: Nursing interventions including high-quality CPR implementation, use of CPR feedback devices, continuous CPR training, and nurse-led resuscitation protocols significantly improved ROSC, enhanced chest compression quality, and increased survival rates among cardiac arrest patients. Conclusion: High-quality CPR–based nursing interventions are effective in improving clinical outcomes of cardiac arrest patients. Strengthening emergency and critical care nurses’ competencies through continuous training and evidence-based protocols is strongly recommended. Suggestion: Heathcare facilities can integrate high-quality CPR Standars into estabilished nursing protocols, particulary by utilizing feedback technology in emergency and criticals care units to ensure consistent compression quality.   Keywords: Cardiac Arrest; Critical Care Nursing; Emergency Department (ER); High-Quality Cardiopulmonary Resuscitation (CPR).   Pendahuluan: Henti jantung merupakan kondisi kegawatdaruratan yang membutuhkan tindakan resusitasi segera. Kualitas Cardiopulmonary Resuscitation (CPR) berperan penting dalam menentukan keberhasilan Return of Spontaneous Circulation (ROSC) dan survival pasien. Perawat gawat darurat dan kritis memiliki peran strategis sebagai penolong pertama dalam pelaksanaan CPR, namun variasi kualitas tindakan masih menjadi tantangan dalam praktik klinik. Tujuan: Untuk mengetahui efektivitas high-quality CPR terhadap survival pasien henti jantung di IGD dan perawatan kritis. Metode: Systematic review yang disusun berdasarkan panduan PRISMA. Pencarian artikel dilakukan melalui database PubMed, Scopus, CINAHL, ScienceDirect, dan Google Scholar pada periode 2019–2024. Artikel yang memenuhi kriteria inklusi dianalisis secara sistematis dan dinilai kualitas metodologinya menggunakan Joanna Briggs Institute (JBI) Critical Appraisal Tool. Hasil: Intervensi keperawatan berupa pelaksanaan high-quality CPR, penggunaan feedback device, pelatihan CPR berkelanjutan, serta penerapan nurse-led resuscitation protocol terbukti meningkatkan ROSC, kualitas kompresi dada, dan survival pasien henti jantung. Simpulan: Intervensi keperawatan berbasis high-quality CPR efektif meningkatkan outcome klinis pasien henti jantung. Oleh karena itu, penguatan kompetensi perawat melalui pelatihan dan penerapan protokol berbasis bukti sangat direkomendasikan. Saran: Fasilitas pelayanan kesehatan dapat mengintegrasikan standar high-quality CPR ke dalam protokol tetap keperawatan, khususnya dengan memanfaatkan teknologi feedback device di unit gawat darurat dan perawatan kritis guna menjamin kualitas kompresi yang konsisten   Kata Kunci: Henti Jantung; High-Quality Cardiopulmonary Resuscitation (CPR); Instalasi Gawat Darurat (IGD); Keperawatan Kritis.